Genome wide association analysis in a mouse advanced intercross line. Issue 1 (December 2018) - Gonzales, Natalia; Seo, Jungkyun; Hernandez Cordero, Ana; St. Pierre, Celine; Gregory, Jennifer; Distler, Margaret; Abney, Mark; Canzar, Stefan; Lionikas, Arimantas; Palmer, Abraham
Abstract The LG/J x SM/J advanced intercross line of mice (LG x SM AIL) is a multigenerational outbred population. High minor allele frequencies, a simple genetic background, and the fully sequenced LG and SM genomes make it a powerful population for genome-wide association studies. Here we use 1, 063 AIL mice to identify 126 significant associations for 50 traits relevant to human health and disease. We also identify thousands ofcis- andtrans- eQTLs in the hippocampus, striatum, and prefrontal cortex of 200 mice. We replicate an association between locomotor activity andCsmd1, which we identified in an earlier generation of this AIL, and show thatCsmd1 mutant mice recapitulate the locomotor phenotype. Our results demonstrate the utility of the LG x SM AIL as a mapping population, identify numerous novel associations, and shed light on the genetic architecture of mammalian behavior. Multigenerational outbred populations from an advanced intercross line (AIL) of mice represent useful resources for genome wide association analysis. Here, the authors analyze 1, 063 LG x SM AIL mice to identify significant associations for 50 traits relevant to human health and disease.